Enlarged airspaces in the distal lung in adolescents born very preterm as measured by aerosol - Per Wollmer; Cecilia Hagman; Madeleine Petersson Sjögren; Jakob Löndahl; Ellen Tufvesson; Hugo Öhrneman; Frida Lindström; Jenny Rissler (BMJ Open Respiratory Research)
Rationale Preterm infants diagnosed with bronchopulmonary dysplasia (BPD) are thought to have fewer and larger alveoli than their term peers, but it is unclear to what degree this persists later in life.Objectives To investigate to what degree the distal airspaces are enlarged in adolescents born preterm and to evaluate the new Airspace Dimension Assessment (AiDA) method in investigating this group.Methods We investigated 41 adolescents between 15 and 17 years of age, of whom 25 were born very preterm (a gestational age <31 weeks, with a mean of 26 weeks) and 16 were term-born controls. Of the preterms, 17 were diagnosed with BPD. The AiDA method was used to measure the average distal airspace radius (rAiDA) in the lungs. In addition, lung function was evaluated by spirometry, impulse oscillometry and diffusing capacity of carbon monoxide (DLCO).Measurements and main results We observed a mean rAiDA of 295±53 µm for the preterm group compared with 231±12 µm for the control group (p<0.0001). The adolescents diagnosed with BPD had a mean rAiDA of 313±54 µm. There was a strong negative correlation between gestational age and distal airspace radius (p<0.0001). The BPD group had a decreased FEV1 (forced expiratory volume in 1 s, z-score: −1.28±1.37, p=0.012) and DLCO (z-score: −0.92±1.01, p=0.013) compared with the controls, but all other lung function variables showed normal values.Conclusions Our results suggest that the enlarged airspaces seen in preterm infants likely remain in adolescence. Distal airspace radius as measured by AiDA was the lung function variable that showed the most significant difference between preterm and term-born adolescents.